The Influence of Socio-Demographic Factors on the Economic Growth of Gorontalo Province - Sultan Dahlim Kadir; Sri Endang Saleh; Herwin Mopangga (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the influence of socio-demographic factors—including education level, labor force participation rate (LFPR), and population size—on economic growth in Gorontalo Province during the 2020–2024 period. The study uses secondary data obtained from the official publications of the Central Bureau of Statistics (BPS) of Gorontalo Province. Data analysis was conducted using a panel data model with the Fixed Effect Model (FEM) approach through the Eviews 12 software. The results show that, partially, education level and population size have a positive and significant effect on economic growth, while the LFPR has no significant effect. Simultaneously, the three independent variables significantly influence economic growth, with the model contributing 99.9%. These findings indicate that improving education quality and strengthening the structure of the productive-age population are crucial factors in driving economic growth in Gorontalo Province. Meanwhile, the high LFPR has not yet provided optimal impact because most of the workforce is still absorbed in low-productivity sectors. This study is expected to serve as a basis for local governments in formulating economic development policies oriented toward improving human resource quality and effectively leveraging the demographic bonus.